The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/pcc.0b013e318253c80e
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Analgesia in Mechanically Ventilated Children

Abstract: Objective To examine the clinical factors associated with increased opioid dose among mechanically ventilated children in the Pediatric Intensive Care Unit (PICU). Design Prospective, observational study with 100% accrual of eligible patients. Setting Seven PICUs from tertiary-care children’s hospitals in the Collaborative Pediatric Critical Care Research Network. Patients 419 children treated with morphine or fentanyl infusions. Interventions None Measurements and Main Results Data on opioid use, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 50 publications
1
26
1
Order By: Relevance
“…Emerging evidence has shown that when used as an infusion it is more favorable than fentanyl with regard to need for dose escalation, incidence of withdrawal, and length of hospital stay. (31, 32) Opioid tolerance and withdrawal pose major challenges for all providers in the PICU, and the predilection for fentanyl may be a trend that needs further evaluation through a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that when used as an infusion it is more favorable than fentanyl with regard to need for dose escalation, incidence of withdrawal, and length of hospital stay. (31, 32) Opioid tolerance and withdrawal pose major challenges for all providers in the PICU, and the predilection for fentanyl may be a trend that needs further evaluation through a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study found that the primary outcome of doubling of daily medication dose (tolerance) was more likely to occur with infusions lasting >7 days. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of studies have described the development of opioid tolerance in children. Recently, Anand et al [16] reported that the fentanyl dose for analgesia and sedation of mechanically ventilated children had to be doubled in 16% of patients after 7 days of opioid exposure. There are no paediatric studies investigating remifentanil escalations to maintain a defined opioid effect.…”
Section: Discussionmentioning
confidence: 99%